1984
DOI: 10.1111/j.1748-1716.1984.tb07515.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GM1 ganglioside treatment on the recovery of dopaminergic nigro‐striatal neurons after different types of lesion

Abstract: The effect of GM1 ganglioside treatment on the recovery of biochemical and behavioral parameters which define the activity of nigro-striatal dopaminergic systems has been investigated in rats after different types of lesion. GM1 favours the recovery of tyrosine-hydroxylase activity, of the number and affinity of 3H-N-n-propyl-norapomorphine binding sites in the striatum of the lesioned side and reduces the apomorphine-induced rotational behavior after mechanical (i.e. unilateral hemitransection) but not after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(17 citation statements)
references
References 38 publications
0
14
0
3
Order By: Relevance
“…Thus, it appears that GM1 does not prevent the lesion, but rather promotes the recovery of the DA content. Recovery may not be the consequence of neuronal sprouting, as has been reported for some surgical lesions (unilateral hemisection) of dopaminergic neurons treated with GM 1 (Toffano et al, 1984), as there was no return of DA uptake in the lesioned animals treated with GM 1. Apparently, the dopaminergic neurons that remain after the lesion synthesize more DA under the influence of GM 1.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Thus, it appears that GM1 does not prevent the lesion, but rather promotes the recovery of the DA content. Recovery may not be the consequence of neuronal sprouting, as has been reported for some surgical lesions (unilateral hemisection) of dopaminergic neurons treated with GM 1 (Toffano et al, 1984), as there was no return of DA uptake in the lesioned animals treated with GM 1. Apparently, the dopaminergic neurons that remain after the lesion synthesize more DA under the influence of GM 1.…”
Section: Discussionmentioning
confidence: 54%
“…GM1 ganglioside has been reported to promote the recovery of cholinergic (Wojcik et al, 1982;Sofroniew et al, 1986), serotonergic Fusco et al, 1986;, adrenergic , and dopaminergic (Toffano et al, 1984;Agnati et al, 1985; activity in the CNS following surgical and neurotoxin lesions. There are also reports of recovery in peripheral tissues following lesions (Caccia et al, 1979;Sparrow and Grafstein, 1982;Gorio et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A G, , effect on increasing dopamine synthesis in surviving neurons is further supported by the observation of increased TH activity (i.e., pmol ['4C]dopa formed/TH+ neuron/h) in surviving cultured fetal dopaminergic neurons exposed to MPP+ followed by G,, (Stull et al, 1994). Although chronic G,, treatment has been shown to increase striatal dopamine levels after a number of different types of lesions (Toffano et al, 1984a), this effect seems to be dependent, to a large extent, on the severity of the lesion (Ramirez and Sabel, 1990). GM, was effective in partially restoring striatal dopamine levels and TH activity after partial unilateral hemi-transactions of the medial forebrain bundle, but had no effect on striatal neurochemistry in animals with almost complete lesions (Toffano et al.…”
Section: Discussionmentioning
confidence: 86%
“…However, the protective or regenerative effects of gangliosides following the administration of cytotoxicants in the CNS are not well estab-lished. Under some experimental conditions, gangliosides appear to be ineffective against the effects of 6-hydroxydopamine [Toffano et al, 1984;Agnati et al, 19851, although GM1 gangliosides have been reported to enhance the regrowth of noradrenaline nerve terminals in cerebra1 cortex of rats exposed to 6-hydroxydopamine [Kojima et al, 19841. Recently, it was reported that GM1 ganglioside treatment attenuated the behavioral effects of colchicine administered directly into the dentate gyrus of the hippocampus of the rat [Emerich et al, 19851.…”
Section: Introductionmentioning
confidence: 99%